IMPLEMENTASI KEBIJAKAN PELAYANAN KESEHATAN IBU DAN ANAK DI KABUPATEN TAKALAR PROVINSI SULAWESI SELATAN - tiah, Halwa (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
Takalar district, South Sulawesi has a policy of maternal and child healthby adopting indigenous shaman a major role in the birthing process in theform of Regulation No. 2 of 2010 on the Partnership midwife and healer.Based on the subject matter, the question of the proposed research is howthe implementation of policies on Maternal and Child Health in Takalardistrict, South Sulawesi? How to model Policy Implementation Maternaland Child Health Care according to local conditions in the district of SouthSulawesi Takalar? The method used is descriptive qualitative. The resultsshowed that the results are good policy performance. The success of thepolicy program at the district MCH-KBD Takalar this policy to be a "pilotproject"for other regions. The contents of the policy is a creative solutionbased on local wisdom for facts on the ground people still believe their role.Program planning, implementation and evaluation are participatorystakeholders. Policy context, the views of the Situational factors, KBD is aform of cooperation with the shaman's midwife with the principle of mutualbenefit sipakatau sipakainge upheld by society Takalar. This principle isimplemented by creating the principle of openness, equality, and trust in anattempt to save the mother and baby. This partnership puts birth attendantsand midwives as their role from birth attendant became a partner in caringfor mothers and babies. In terms of structural factors, contextually seen thatthe decentralization policy in the health sector in the district Takalar hasbeen used for the benefit of policy implementation KIA. KBD policy islocal policy is based on local cultural values and fully supported bystakeholders.Keywords: Implementation, health care, mother and child, shaman, Takalar